Actions of l-thyroxine and Nano-diamino-tetrac (Nanotetrac) on PD-L1 in cancer cells - Hung‐Yun Lin; Yu‐Tang Chin; André Wendindondé Nana; Ya‐Jung Shih; Hsuan‐Yu Lai; Heng‐Yuan Tang; Matthew C. Leinung; Shaker A. Mousa; Paul J. Davis (2016)
The PD-1 (programmed death-1)/PD-L1 (PD-ligand 1) checkpoint is a critical regulator of activated T cell-cancer cell interactions, defending tumor cells against immune destruction. Nano-diamino-tetrac (NDAT; Nanotetrac) is an anticancer/anti-angiogenic agent targeted to the thyroid hormone-tetrac receptor on the extracellular domain of integrin αvβ3. NDAT inhibits the cancer cell PI3-K and MAPK signal transduction pathways that are critical to PD-L1 gene expression. We examined actions in vitro of thyroid hormone (l-thyroxine, T4) and NDAT on PD-L1 mRNA abundance (qPCR) and PD-L1 protein content in human breast cancer (MDA-MB-231) cells and colon carcinoma (HCT116 and HT-29) cells. In MDA-MB-231 cells, a physiological concentration of T4 (10−7 M total; 10−10 M free hormone) stimulated PD-L1 gene expression by 38% and increased PD-L1 protein by 2.7-fold (p < 0.05, all changes). NDAT (10−7 M) reduced PD-L1 in T4-exposed cells by 21% (mRNA) and 39% (protein) (p < 0.05, all changes). In HCT116 cells, T4 enhanced PD-L1 gene expression by 17% and protein content by 24% (p < 0.05). NDAT reduced basal PD-L1 mRNA by 35% and protein by 31% and in T4-treated cells lowered mRNA by 33% and protein by 66%. In HT-29 cells, T4 increased PD-L1 mRNA by 62% and protein by 27%. NDAT lowered basal and T4-stimulated responses in PD-L1 mRNA and protein by 35–40% (p < 0.05). Activation of ERK1/2 was involved in T4-induced PD-L1 accumulation. We propose that, by a nongenomic mechanism, endogenous T4 may clinically support activity of the defensive PD-1/PD-L1 checkpoint in tumor cells. NDAT non-immunologically suppresses basal and T4-induced PD-L1 gene expression and protein accumulation in cancer cells.